Factors associated with ABCDEF bundle implementation for critically ill patients: An international cross-sectional survey in 54 countries - Junpei Haruna; Takeshi Unoki; Keibun Liu; Kensuke Nakamura; Shigeaki Inoue; Osamu Nishida (SAGE Open Medicine)
Objectives: This study investigated the implementation of the ABCDEF bundle and the factors associated with its implementation according to national income levels. Methods: This study is cross-sectional research. We conducted a secondary analysis of an international 1-day point-prevalence study that investigated the implementation of the ABCDEF bundle in critically ill patients. All patients admitted to the ICU were eligible. This study was conducted across 135 ICUs in 54 countries, including data from 664 patients. Outcomes were categorized according to the income level of the country (high-income, middle-income, and low-income countries) in which each ICU was located. A multilevel generalized linear model was developed to identify the factors associated with ABCDEF bundle implementation for each income level. Results: We identified 664 patients in 79 high-income countries, 278 in 26 middle-income countries, and 287 in 30 low-income countries ICUs. Implementation rates of the ABCDEF bundle were low for all income levels but varied. Few individuals completed the entire bundle on the survey date. Common factors associated with the implementation among all income levels were a multidisciplinary team approach for Element A (pain) and mechanical ventilation use for Element C (sedation), which were also associated with lower Element E (mobility). The existence of a protocol was frequently identified as a promoting factor associated with ABCDEF bundle implementation. The associated factors varied by income level; for example, dedicated intensivists were only identified in high-income countries, but not in middle-income countries or low-income countries. Conclusions: The overall low ABCDEF bundle implementation rates necessitate action. As factors associated with its implementation vary according to national income level, tailored strategies are essential for improving ICU care quality. Trial registration: NA.